2014
DOI: 10.15376/biores.10.1.760-771
|View full text |Cite
|
Sign up to set email alerts
|

Temperature/pH Sensitive Cellulose-based Hydrogel: Synthesis, Characterization, Loading, and Release of Model Drugs for Potential Oral Drug Delivery

Abstract: Due to their unique physical and chemical properties, hygrogels have been applied in various industrial and agricultural fields. Biomedicine is another high value-added and attractive area for the application of hydrogels. For this reason, a novel temperature/pH sensitive cellulose based hydrogel was synthesized based on the cellulose from Phyllostachys heterocycla. Its synthesis conditions were optimized, and its loading and release capabilities for model drugs were investigated in detail. The resultant data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Zhou et al synthesized cellulose based temperature/pH sensitive hydrogels for controlled oral drug delivery of model drug, methylene blue/methylene orange. The as-prepared hydrogels exhibited excellent pH sensitivity and showed swelling at pH 7.4 [ 90 ].…”
Section: Base Materials For Ph Sensitive Hydrogelsmentioning
confidence: 99%
“…Zhou et al synthesized cellulose based temperature/pH sensitive hydrogels for controlled oral drug delivery of model drug, methylene blue/methylene orange. The as-prepared hydrogels exhibited excellent pH sensitivity and showed swelling at pH 7.4 [ 90 ].…”
Section: Base Materials For Ph Sensitive Hydrogelsmentioning
confidence: 99%
“…The release of a model molecule (dimethyl methylene blue) showed that these systems are promising smart materials for drug delivery [329]. In addition, to being thermoresponsive, NIPAAm/cellulose showed pH-responsiveness as these hydrogels showed higher water uptake capacities at alkaline pHs than at acidic pHs [330]. Bajpai et al developed a polyacrylic acid, and carboxymethyl cellulose semi interpenetrated polymer network for the controlled release of ciprofloxacine [331].…”
Section: Cellulose-based Hydrogels For Drug Deliverymentioning
confidence: 99%
“…Zhou et al found that cellulose extracted from bamboo (Phyllostachys heterocycla) shows high swelling rates at human body temperature and intestinal pH. Thus, hydrogels based on this cellulose exhibit an immense potential as an oral drug model [159]. According to Sannino et al, edema problems can also be treated using cellulose-based hydrogels as these systems have improved water absorbing and holding capacity [160].…”
Section: Hydrogels In Biomedicinementioning
confidence: 99%